2005
DOI: 10.1049/el:20057956
|View full text |Cite
|
Sign up to set email alerts
|

Giant linewidth enhancement factor and purely frequency modulated emission from quantum dot laser

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 6 publications
3
46
1
Order By: Relevance
“…. 5 are commonly measured, the measured α-factors in quantum-dot lasers range from near-zero [NEW99a,KON04a,ALE07] to very high values [DAG05], and even "infinite" α [CON07,GRI08a]. Furthermore, a strong dependence on the pump current has been observed [SU05a,JIA12].…”
Section: Amplitude-phase Coupling In Quantum-dot Lasersmentioning
confidence: 99%
“…. 5 are commonly measured, the measured α-factors in quantum-dot lasers range from near-zero [NEW99a,KON04a,ALE07] to very high values [DAG05], and even "infinite" α [CON07,GRI08a]. Furthermore, a strong dependence on the pump current has been observed [SU05a,JIA12].…”
Section: Amplitude-phase Coupling In Quantum-dot Lasersmentioning
confidence: 99%
“…2,3 Recent analysis has shown that the low ground state ͑GS͒ gain saturation of QD devices coupled with a large amount of nonresonant carriers in the QD's excited states ͑ES͒ and barrier states can result in large values above threshold 4 and as a consequence, directly phase modulated devices have been demonstrated. 5 In addition, it has been proposed that the unique carrier dynamics of QD semiconductor optical amplifiers ͑SOAs͒ would lead to a reduction of patterning effects compared to conventional devices, for both linear and nonlinear applications. 6,7 As the understanding of relevant carrier relaxation processes in QD structures improves, additional device functionalities will be realized.…”
mentioning
confidence: 99%
“…When the control signals A and/or B are fed into the two SOAs they modulate the gain of the SOAs and give rise to the phase modulation of the co-propagating CW signal due to LEF α Agrawal (2001), Agrawal (2002), Newell (1999. LEF values may vary in a large interval from the experimentally measured value of LEF α = 0.1 in InAs QD lasers near the gain saturation regime Newell (1999) up to the giant values of LEF α = 60 recently measured in InAs/InGaAs QD lasers Dagens (2005). However, such limiting cases can be achieved for specific electronic band structure Newell (1999), Dagens (2005), Sun (2004).…”
Section: Theoretical Approachmentioning
confidence: 96%